THE USE OF CARBON DIOXIDE FOR COLD TREATMENT OF POULTRY CARCASSES - Neverov E.N. (Техника и технология пищевых производств)
Now demand for the cooled turkey meat grew considerably as it possesses the increased power value, balance of protein composition, availability of biologically active agents, high bioavailability, it is also considered dietary. Turkey meat retains its useful properties during chilled storage, but the term of its storage is small which imposes certain restrictions when sold. For increasing fowl storage periods the scientists consider a perspective way in which the product is in direct contact with carbon dioxide. Cooling treatment is made by the impact of the cold gas and liquid environment on the product or creating the mixture from gas and the firm CO2 dispersed in it. The plant allowing the supply of snow-like carbon dioxide both onto the surface and into the internal cavity of bird carcasses before their transportation is developed at the HVAC department of the Kemerovo institute of food science and technology (university). It allows cooling and transportation of the product at the same time. The nature of changes in temperature field and heat-removal kinetics in cooling treatment of bird carcasses is investigated. Consumption and time of various option carbon dioxide treatment of turkey carcass surface when cooling are defined. It is established that introduction of the snow-like carbon dioxide into a turkey carcass is justified, since the carbon dioxide placed in the internal cavity of a carcass sublimates substantially due to the warmth which is taken away from the carcass. The snow-like CO2 on the turkey surface takes heat away from the environment as well, that leads to considerable reduction of the sublimation period and the raised carbon dioxide consumption. Thus, carbon dioxide suppresses the action of many microorganisms, and its placement in the internal cavity of a turkey carcass will lead to the increase in term of storage.